DESAIN APLIKASI ABSENSI SANTRI PONDOK ABDUL DHOHIR MENGGUNAKAN PENGENALAN WAJAH BERBASIS WEB - Ardiansyah, Mochamad Dicky; Putri, Anggia Dasa (LPPM Universitas Putera Batam, 2023)
The web-based face recognition application will provide convenience for students to LDII organizations or Islamic boarding school, it is possible for the students themselves to give their best in carrying out their activities. Attendance is crucial to any organization. Where participation is one of the key factors that may encourage and support any action that will take place. Operating the attendance system manually at the moment, namely utilizing manual paper. This might lead to a number of errors.and unhygienic times during the pandemic, example is the inefficiency of utilizing paper, forgetting to fill in the absences, missing paper used and using pens alternately causing the spread of the COVID-19 virus. By using Face Recognition, students only show the face to be scanned using a webcam provided by the boarding school teacher. The strategy utilized in this study is rapid application development using modeling using the Unified Modeling Language (UML). The Django web framework's tools were then used to create this application, Postgresql and Python programming. This application was built with the aim of making it easier for boarding school teacher and students.